Ferroptosis-related lncRNAs as prognostic biomarkers in renal cell carcinoma: a systematic review and meta-analysis - Lin, Jia-Feng; Wu, Zhi-Huang; Zhang, Min-Jie; Luo, Jian-Bin; Chen, Guo-Qiang (Frontiers in Oncology, 2025)
BackgroundAbundant evidences have indicated that long non-coding RNAs (lncRNAs) can be used to evaluate the prognosis of patients with renal cell carcinoma (RCC), and the purpose of this study was to evaluate the association between ferroptosis-related lncRNAs (FRLs) and the prognosis of patients with RCC by means of a meta-analysis.Materials and methodsAll studies assessing the prognosis of patients with FRLs and RCC were collected up to 31 October 2024 by searching databases such as PubMed, Web of Science, Embase, Scopus and Cochrane Library. Pooled analyses were performed on the collected data, including metrics such as gender, age, risk score, tumor stage, and tumor grade. Hazard ratio (HR) and 95% confidence intervals (CI) were employed to assess the outcome metrics. To evaluate the heterogeneity among studies, the I² statistic and Q test were utilized. P < 0.05 was regarded as statistically significant. All data analyses were conducted by Stata 17.0 software and Review Manager 5.4.1.Results19 literatures involving 5974 RCC patients were included in this study. The meta-analysis outcomes indicate that there was no significant correlation between FRLs and the gender of RCC patients (HR = 0.93, 95% CI = 0.85 - 1.03, P = 0.17). However, FRLs were associated with patient age (HR = 1.03, 95% CI = 1.03 - 1.04, P < 0.00001), risk score (HR = 1.05, 95% CI = 1.03 - 1.06, P < 0.00001), tumor grade (HR = 1.46, 95% CI = 1.28 - 1.67, P < 0.00001) and tumor stage (HR = 1.85, 95% CI = 1.68-2.03, P < 0.00001) were significantly correlated. In tumor staging, FRLs were significantly correlated with N-stage (HR = 1.51, 95% CI = 1.10 - 2.08, P = 0.01) and M-stage (HR = 1.80, 95% CI = 1.21 - 2.68, P = 0.004) in patients with RCC, but not significantly correlated with T-stage in patients (HR = 1.34, 95% CI = 0.86 - 2.09, P = 0.19).ConclusionThe findings of this study indicate that the abnormal expression of FRLs in RCC is obviously associated with the prognosis of patients, and that FRLs can be used as a new tumor marker to predict the prognosis of RCC patients with high accuracy.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024610803, identifier CRD42024610803.